Incomplete (rq-q+r- ɛ , r)-arcs and minimal {ℓ,t}-Blocking set in PG(2,q) - Nada Yahya; Hiba najem (Al-Rafidain Journal of Computer Sciences and Mathematics)
We proved that(rq-q+r-ɛ,r)-arcs is incomplete  by using minimal {ℓ,t}-Blocking set in projective plane PG(2,q)and we found a new condition for ɛ is ɛ ≥-A(r-1)2+B(r-1)-C and A,B,C is a constant which is not get previously in studies which is search in finding ɛ  for incomplete (rq-q+r-ɛ,r)-arcs ,for value 2≤r≤ 4  where q is prime for values 11≤q≤ 31  in addition to  q=16.